Optimization Design of Integrated Axle Housing Electromagnetic Clutch with Heavy Load based on Uniform Design Theory - Zhou Hongru (Jixie chuandong)
In order to solve the problems of low transmission efficiency,large moment inertia of new type integrated axle housing electromagnetic clutch with heavy load,the integrated axle housing electromagnetic clutch is regarded as the research object,the uniform design theory and regression analysis are used to completed the optimization design on the structure parameters of the integrated axle housing electromagnetic clutch,finally,the electromagnetic clutch optimized is verified by bench test method. The results show that the optimization of integrated axle housing electromagnetic clutch input shaft speed between the initial value and stable value difference is relatively small,and the engagement time significantly shorter than no optimization of electromagnetic clutch. In addition,the optimized model of electromagnetic clutch force between the disc and friction plate is decreased significantly,which can effectively improve the structural stability of clutch.